Remote-access thyroidectomy with the da Vinci SP system: feasibility in a cadaveric model - Stein, Hubert; Kang, Sang Wook; Heo, Seung Young; Rheinwald, Markus (Frontiers in Surgery, 2023)
Background Study the feasibility of a remote-access thyroidectomy through presternal and submental approaches with the da Vinci SP system. Methods Bilateral thyroidectomies were performed in five cadaveric models. In two cadavers a single incision in the presternal area was used and in three cadavers a submental face lift incision approach. Results Performing remote-access thyroidectomy was completed in one cadaver with a presternal and in three cadavers with the submental approach. The required skin flap development was minimal and docking time for the SP system quick for all procedures. Time to full exposure of the thyroid gland after skin incision was less than 30 min for the presternal approach and below 27 min for the submental procedure. Completing total thyroidectomies took 83 min in the presternal approach and between 67 - 127 min with the submental access. No additional ports were required to expose the gland and complete the bilateral resection. Conclusions Total thyroidectomy was feasible with the da Vinci SP in single incision presternal and submental approaches comparing promisingly with other currently applied robotic methods. Further studies will be required to assess if a presternal or submental thyroidectomy with the da Vinci SP system provides clinical benefits in real patients.